Pengaruh Dana Alokasi Umum, Pendapatan Per Kapita Dan Kemiskinan Terhadap Pendapatan Asli Daerah Kabupaten/Kota Di Provinsi NTT - Kale, Patris Enos Rihi Kana; Nanga, Muana (Jurnal Ilmiah Manajemen Kesatuan, 2015)
The study is aimed to investigate the effect of general purposes transfer (DAU), per capita GRDP and poverty rate on own sources revenue (PAD) for District level in Province of East Nusa Tenggara (NTT). To estimate the effect of DAU, per capita GRDP and poverty rate on PAD, the panel data regression model are used that is model based on panel data (combination of time series and crosssection data); and pooled least squares (PLS), fixed effect model (FEM) and random effect model (REM) methods are used to estimate the regression model. The result shows that all independent variables that is DAU, per capita GDRP and poverty rate has significant statistical effect on PAD in Province of East Nusa Tenggara. The findings in this study has an important policy implication for the regional and central govemment, that is, to increase PAD di regional level, DAU and per capita GRDP should be incrased, and the contrary, poverty reduction in regional level should be continously conducted by the government at all level. Keyword: general purpose transfer, own source revenue